Develop algorithms to determine the status of car drivers using built-in accelerometer and GBDT - Thi Thu Nguyen; Phuc Thinh Doan; Anh-Ngoc Le; Kolla Bhanu Prakash; Subrata Chowdhury; Duc-Nghia Tran; Duc-Tan Tran (Institute of Advanced Engineering and Science, 2022)
In this paper, we introduce a mobile application called CarSafe, in which data from the acceleration sensor integrated on smartphones is exploited to come up with an efficient classification algorithm. Two statuses,